CULTURAL DIFFERENCES IN TRANSLATION AND THEIR IMPACT ON THE PROCESS (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
This article examines the role of cultural differences in the translation process, particularly in translating film titles. It discusses how cultural nuances can affect the way a film is perceived by different audiences and the strategies translators employ to adapt content. These strategies, such as adaptation, addition, omission, and substitution, help maintain the meaning, emotional tone, and cultural relevance of the original text. The article highlights the importance of balancing cultural sensitivity with linguistic accuracy and the commercial considerations involved in translation.